Reusing Learning Objects via Theory Morphisms - Kohlhase, Michael; Schütz, Marcel (Lecture Notes in Computer Science (including subseries Lecture Notes in Artificial Intelligence and Lecture Notes in Bioinformatics), 2024)
One of the most important motivations of module systems for formal systems is that statements and objects can be re-purposed in other contexts via the inheritance pathways. In this paper, we show that this idea can be extended to informal settings using an adaptive learning assistant (ALeA) as a concrete use case. Specifically, we concentrate on repurposing informal definitions, quiz questions, and explanations between the contexts given by different theories in a flexiformal theory graph. Using this, we can now refactor (transport backwards over a theory morphism) e.g. quiz questions like “Is the following formula A satisfiable?” to be logic-independent and utilize them in any logic via forward morphism transport. This goes a large step towards solving the biggest practical problem in ALeA-like systems: provisioning enough targeted semantically annotated learning objects.
CRIS-Team Scopus Importer:2024-08-23